Q-switched fiber lasers with carbon nanotubes hosted in ceramics - Song, Yong-Won (OPTICAL SOC AMER, 2012)
Q-switched fiber ring lasers operated by single-walled carbon nanotubes (SWNTs) hosted in SiO2 matrix are demonstrated by highlighting their stable operation and dramatically improved thermal damage threshold. Employing aerosol deposition process, SWNTs are incorporated into the ceramic host at room-temperature without solubility limitation. After experiencing the intracavity optical power higher than 15.3 dBm, the hosted SWNTs survive to provide Q-switching operation. The continuous repetition rate tuning is achieved in the range of 11.1-32.2 kHz with the pulse-duration of 7.1-15.8 mu s at 1558.5 nm. (C) 2012 Optical Society of America
Keywords: MODE LOCKERS; GLASS